Sustainability Competences A study based in Chalmers Challenge Lab - Hagvall Svensson, Oskar (My University, 2016)
The sustainability challenges of today are complex and wicked, and can therefore not be easily comprehended and solved. In order to handle the complexity – e.g. stemming from lock-ins or conflicts of interests – ‘sustainability competences’ are needed, and subsequently such competences need to be fostered in the engineers of tomorrow. However, research on sustainability competences have yet to converge into an established field and consequently there is no clear consensus on what knowledge, skills and attitudes should be looked upon as crucial for sustainability. With the purpose of contributing to this convergence, aiming to capture the current view in research, this study reviews literature on sustainability competences and finds a synthesis between competences discussed in the fields of education and sustainability, leadership and sustainability and transition management. Moreover, the thesis draws inspiration from Chalmers Challenge Lab – a multi-stakeholder learning environment built around international engineering students undertaking their master’s thesis through designing and implementing strategies to engage in sustainability transitions in a co-creating manner – which is studied through observations and interviews, in order to enrich the understanding of sustainability competences. In investigating Challenge Lab’s contribution to this field, the study takes on the notion of learning through adaption, metaphorically viewing earlier research as an entity ‘learning’ from interaction with the phenomena Challenge Lab. Accordingly, the knowledge of sustainability competences found in earlier research is seen as held in a metaphorical ‘cognitive structure’, which is enriched with new understanding through accommodation and assimilation caused by the interaction with a new object of study, i.e. the Lab itself. The metaphorical structures are represented by frameworks of categories for sustainability competences, developed through a general inductive analysis procedure. The study shows support in earlier research for at least nine categories of competences relevant for working with sustainability, namely systems-thinking, anticipatory competence, normative competence, strategic competence, interpersonal competence (Wiek et al., 2011), intrapersonal competence, being and owning, trans-rational thinking and leading with others. These seem to be intricately interlinked. However, it remains to be determined which of the categories can be looked upon as ‘key’ competences for sustainability. Also, there are major similarities in the competence categories identified from earlier research, the competences that Challenge Lab aim to foster and the perceived competence development of the Challenge Lab students. Moreover, differences and similarities between earlier research and perspectives on sustainability competences at Challenge Lab point towards further clarification and justification of anticipatory competences, intrapersonal competences and specific attitudinal aspects (being and owning), as well as further investigation of less tangible ways of understanding systems and challenges (trans-rational thinking), and collective leadership competences guided by theories of emergence and complexity (leading with others) as potential areas of development for sustainability competence theory.
Keywords: Informationslära; Information science